2018
DOI: 10.5222/head.2018.222
|View full text |Cite
|
Sign up to set email alerts
|

Determining the knowledge and opinions of nurses and midwives working in gynecology clinics about natural birth and interventions during birth

Abstract: Amaç: Kadın doğum kliniklerinde çalışan hemşirelerin ve ebelerin doğal doğum ve doğumda uygulanan müdahaleler hakkındaki bilgi ve görüşlerini belirlemektir. Yöntem: Araştırmanın örneklemini, İzmir ilinde bir hastanenin Kadın Hastalıkları ve Doğum Kliniklerinde çalışan 106 hemşire ve ebe oluşturmuştur. Veriler, çalışanlara ait tanıtıcı bilgilerin de yer aldığı, doğal doğum ve doğumda uygulanan müdahaleler hakkında literatür doğrultusunda hazırlanmış veri toplama formu ile Temmuz-Aralık 2016 tarihleri arasında t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In line with the central limit theorem, the sample volume is above 30, indicating that the distribution is close to the normality. As the sample volume was 170, it can be concluded that the distribution is not normal (Gürsakal, 2013). It was decided to carry out normal distribution analyzes for the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the central limit theorem, the sample volume is above 30, indicating that the distribution is close to the normality. As the sample volume was 170, it can be concluded that the distribution is not normal (Gürsakal, 2013). It was decided to carry out normal distribution analyzes for the study.…”
Section: Resultsmentioning
confidence: 99%
“…The answers given to the question were single with 61.5%, the married participants stated that they were important with 53.8%. In the other literature, which proves the importance of privacy, 15.1% of nurses and midwives think that an appropriate environment should be provided for an ideal delivery room (that the patient's relatives can enter, and patient privacy is provided (Güleç et al, 2018). (Duman, 2006) in his study, he specified that all participants stated that the cost of caesarean delivery is higher.…”
Section: 371mentioning
confidence: 99%